Editorial Message - Editor in Chief (Baneshwor Campus Journal of Academia, 2025)
With pleasure comes the announcement and publication of Volume 4 (2025) of the Baneshwor Campus Journal of Academia. This annual publication represents the collective and concerted scholarly contribution by the Research Management Committee of the Baneshwor Multiple Campus in the subject of national and international academic discourse and the commitment to the ethics of excellence and multidisciplinary pursuits.